The Role of Gut Microbiota-Bile Acids Axis in the Progression of Non-alcoholic Fatty Liver Disease - Ni, Yiming; Lu, Mengna; Xu, Yuan; Wang, Qixue; Gu, Xinyi; Li, Ying; Zhuang, Tongxi; Xia, Chenyi; Zhang, Ting; Gou, Xiao-jun; Zhou, Mingmei (Frontiers in Microbiology, 2022)
Nonalcoholic fatty liver disease (NAFLD), an emerging global health problem affecting 25%-30% of the total population, refers to excessive lipid accumulation in liver accompanied by insulin resistance (IR) in people with no significant alcohol intake. The increasing prevalence of NAFLD will lead to an increasing number of cirrhosis, as well as hepatocellular carcinoma (HCC) requiring liver transplantation, and the treatment of NAFLD and its advanced diseases is suboptimal. Accordingly, it is necessary to find signaling pathways and targets related to the pathogenesis of NAFLD for the development of novel drugs. A large number of studies and reviews have described the key function of bile acids (BAs) and their receptors in the pathogenesis of NAFLD; the gut microbiota (GM), of which composition varies between healthy and NAFLD patients, can contribute to the transformation of more than 50 kinds of secondary bile acids, and involved in the pathophysiology of NAFLD through the GM-BAs axis. Correspondingly, BAs have the ability to inhibit the overgrowth of GM and have a potent anti-microbial role in maintaining a healthy gut. Here we review the biosynthesis, enterohepatic circulation and major receptors of BAs, as well as the relationship of GM, BAs and the pathogenesis in different disease progression of NAFLD. This article also reviews several therapeutic approaches for the management and prevention of NAFLD targeting the GM-BAs axis.